Os efeitos da integração das áreas de marketing e operações para as organizações - Piaz, Juliana Lúcia Accordi Ferrari Dal (Universidade do Vale do Rio do Sinos, 2006)
Despite the evident relevance of the integration between different functional areas, rare are the cases that contemplate the effect of this integration in the performance of the organizations. The most frequent approach is related to the nature of the existing conflicts, to the analysis of the barriers that make difficult the integration or the mechanisms that facilitate its occurrence. The present work looked for analyzing the impact of the relation between the operational and marketing areas concerning customer’s satisfaction. So a study about the furniture industry was performed, using three companies of the sector as source of data, located in the city of Bento Gonçalves/Rio Grande do Sul, which is considered as an important region of the sector. The method was based on the accomplishment of two researches of qualitative nature, the first one to evaluate the existence and the level of integration between the operational area and the marketing area, while the second one to evaluate, among the customers of
Keywords: integração de áreas; operações; satisfação de clientes; marketing; customer’s satisfaction; integration; operations; Ciências Sociais Aplicadas